Attenuation of Yersinia pestis fyuA Mutants Caused by Iron Uptake Inhibition and Decreased Survivability in Macrophages - Chen, Yulu; Song, Kai; Chen, Xin; Li, Ye; Lv, Ruichen; Zhang, Qingwen; Cui, Yujun; Bi, Yujing; Han, Yanping; Tan, Yafang; Du, Zongmin; Yang, Ruifu; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Yersinia pestis is the etiological agent of plague, a deadly infectious disease that has led to millions of deaths throughout history. Obtaining iron from the host is very important for the pathogenicity of bacteria. Y. pestis has many iron uptake systems. Yersiniabactin (Ybt) plays major roles in iron uptake in vivo and in vitro, and in virulence to mice. FyuA, a β-barrel TonB-dependent outer membrane protein, is the receptor for Ybt. In this study, we examined the importance of the fyuA gene for Y. pestis virulence in different mouse models and explored the related mechanisms. The BALB/c mouse infection assay showed that the virulence of mutant strains (ΔfyuA and ΔfyuAGCAdel) was decreased in comparison with that of strain 201 wild-type (WT), and that the attenuation of virulence of mutant strains through subcutaneous and intraperitoneal challenges was much greater than that through intravenous injection. Iron supplementation could restore lethality during subcutaneous challenge with the two mutants. Thus, we speculated that the attenuated virulence of the mutant strains to mice may be caused by dysfunctional iron uptake of the mutants. Besides, ΔfyuA and ΔfyuAGCAdel strains showed lower survival rates in murine macrophage RAW264.7 cells, which may be another reason for the attenuation. We further explored the transcriptomic differences between WT and mutant strains at different temperatures. We found that the expression of genes related to Ybt synthesis and its regulation was significantly downregulated in mutant strains, indicating that fyuA may have a regulatory effect on Ybt. In addition, the expression of components of the type III secretion system (T3SS) in mutants was unexpectedly upregulated, which was inconsistent with the traditional view of the upregulation of virulence genes increasing the virulence of pathogens.